Pelatihan Pemandu Wisata Dan Bahasa Inggris Pariwisata Di Desa Wisata Medewi Jembrana - Antara, Ida Bagus Ketut Soma; Nirmalasari, Ni Luh Putu Intan; Koeswiryono, Dika Pranadwipa (Jurnal Pengabdian kepada Masyarakat Radisi, 2023)
Tourist villages are a forum for local communities to participate in regional tourism development. Through the existence of tourist villages, people can develop their potential and it is hoped that this can improve the welfare of local communities. Medewi Village is a tourist village known as an international surfing location. However, the results of these tourism activities have not had a massive impact on the community in Medewi Village. The formation of the Medewi Tourism Village is expected to have a wider impact, but this cannot yet be done optimally because efforts are needed to increase public awareness about tourism. To increase public awareness, training and assistance is needed so that people are more aware of tourism and have the ability to manage their tourism potential. Assistance activities carried out include English language training and tour guiding so that the community has competence in communicating and accompanying tourists while visiting the Medewi Tourism Village. This service is carried out through three stages, including needs analysis, data collection and implementation of training activities.